Pengaruh Pengungkapan Kinerja Keberlanjutan, Efisiensi Operasional dan Leverage terhadap Stabilitas Keuangan - Katiandagho, Intishar Ghinawijaya; Dewi, R Rosiyana (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to test and analyze the impact of Sustainability Dimension Disclosure consisting of Economic Dimension, Social Dimension, and Environmental Dimension as well as Operational Efficiency and Leverage on the Financial Stability of Energy Sector Companies in Indonesia. The assessment of the quality of the hunting dimension is carried out using the POJK Number 51 / POJK.03 / 2017 assessment index, Operational Efficiency is obtained by looking at the proportion of operational expenses to operational income while Leverage is obtained using the DAR calculation. This study is based on an analysis of panel data on the desire performance indicators and financial data of 65 Energy Sector Companies listed on the Indonesia Stock Exchange during 2021-2023. All data are obtained from the Sustainability Report and Integrated Annual Report, while financial data are obtained from the Financial Statements. The results found that Disclosure of Economic, Social, and Environmental Dimensions as well as Operational Efficiency have no effect on Financial Stability, but Leverage has a significant negative effect on Financial Stability.